Sport in society : - Coakley, Jay J. (McGraw-Hill, 2015)
The book is the definitive text for the sport sociology course. Taking a global, issues-oriented approach to study the role of sport in society, this text encourages the discussion of current sports-related controversies and helps students develop critical thinking skills.